2001
DOI: 10.2337/diacare.24.11.1961
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Soluble Adhesion Molecules and Insulin Sensitivity in Type 2 Diabetic Individuals

Abstract: OBJECTIVE -The purpose of this study was to explore the relation between insulin resistance and plasma levels of soluble adhesion molecules and to examine the effects of acute hyperinsulinemia on these molecules in type 2 diabetic individuals.RESEARCH DESIGN AND METHODS -Intercellular adhesion molecule (ICAM)-1, vascular cell adhesion molecule (VCAM)-1, and E-and P-selectin plasma concentrations were measured in 36 nonobese type 2 diabetic patients without cardiovascular disease and in 7 healthy subjects. Insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
27
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 31 publications
7
27
1
1
Order By: Relevance
“…However, unlike the previous report (30) demonstrating significant sex differences in soluble adhesion molecules in a large sample of middle-aged men and women (aged 40 -59 years), we observed a sex difference in VCAM-1 levels in blacks only (boys: 378.9 Ϯ 20.0 vs. girls: 450.7 Ϯ 22.7, P ϭ 0.028). In addition, the observation that in whites the relationship between insulin sensitivity, ICAM-1, and E-selectin levels disappears after controlling for VAT is consistent with Targher et al (31), who reported a similar finding in Caucasian adults with type 2 diabetes. These findings suggest that excess adiposity may contribute to increased circulating levels of adhesion molecules.…”
Section: -The Prevalence Of the Individual Components Of Metabolic Sysupporting
confidence: 79%
“…However, unlike the previous report (30) demonstrating significant sex differences in soluble adhesion molecules in a large sample of middle-aged men and women (aged 40 -59 years), we observed a sex difference in VCAM-1 levels in blacks only (boys: 378.9 Ϯ 20.0 vs. girls: 450.7 Ϯ 22.7, P ϭ 0.028). In addition, the observation that in whites the relationship between insulin sensitivity, ICAM-1, and E-selectin levels disappears after controlling for VAT is consistent with Targher et al (31), who reported a similar finding in Caucasian adults with type 2 diabetes. These findings suggest that excess adiposity may contribute to increased circulating levels of adhesion molecules.…”
Section: -The Prevalence Of the Individual Components Of Metabolic Sysupporting
confidence: 79%
“…There is substantial evidence indicating that inflammatory cytokines act through paracrine and autocrine mechanisms to induce insulin resistance [33,34]. Nevertheless, there are conflicting reports on the usefulness of their circulating concentrations to detect this process, and several studies have failed to identify relationships between serum markers of inflammation and measures of insulin resistance [35], especially when the correlations were controlled for the influence of obesity [36,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…intercellular adhesion molecule-1, P-selectin, and E-selectin) than those without the syndrome (142)(143)(144)(145). Moreover, increased endothelial cell microparticles (EMP) release, platelet and leukocyte hyperactivation, increased binding of both EMPs and platelets to leukocytes are also shown in patients with the metabolic syndrome (133,146).…”
Section: Hypercoagulability and Hypofibrinolysismentioning
confidence: 95%